Workers’ health in Intensive Care Units: a systematic review (Saúde Ética & Justiça, 2022)
Introduction – The ICUs (Intensive Care Units) are hospital areas dedicated to critically ill patients who need continuous assistance and monitoring. The work in ICUs has its own characteristics and impacts workers’ health in particular ways. Objective - to verify the organizational factors that may contribute to illness, the most studied professional categories and health problems, as well as the interventions that have been carried out with workers to promote work-related health. Method – A systematic review of articles published between 2015 and 2021 about the health of ICU professionals in Brazil. Results – A total of 38 scientific publications were analyzed and categories were created to better present the data. Conclusion – Expressive rates of burnout and musculoskeletal complaints were found among ICU professionals. Nursing assistants were the most affected professional category. Among the factors that favor illness were organizational aspects, work overload, lack of resources and personnel, and low pay. Studies reporting interventions were scarce in the researched literature.